Nutritional treatment as an essential element of oncological therapy - Bielak, Kamil; Kamińska, Katarzyna; Bielak, Alicja; Łopacka-Szatan, Karolina; Świstak, Marzena; Kamińska, Marzena (Medycyna Paliatywna/Palliative Medicine, 2025)
Nutritional therapy is an essential element of comprehensive oncological therapy, directly impacting the effectiveness of anticancer treatment and patients’ quality of life. Malnutrition affects 40–80% of cancer patients and is a major prognostic factor. The aim of this study is to comprehensively analyse contemporary nutritional treatment methods in oncology, with particular emphasis on oral supplementation, enteral nutrition (EN), and parenteral nutrition, and to assess their effectiveness in various phases of oncological therapy. A systematic literature review was conducted, encompassing current data from PubMed, Google Scholar, and the latest guidelines from international scientific societies (ESPEN, ASCO, ASPEN). Seventy-eight scientific publications 2018–2024 were analysed, with a particular focus on randomised controlled trials and clinical guidelines. Contemporary nutritional treatment in oncology is based on early identification of malnutrition using the Global Leadership Initiative on Malnutrition (GLIM) criteria and the patient-generated subjective global assessment scale. Oral nutritional supplementation is a first-line treatment, demonstrating effectiveness in improving body weight, reducing treatment toxicity, and improving quality of life. Enteral nutrition is indicated in patients with insufficient oral intake of > 60% of requirements for > 7–14 days. Parenteral nutrition is used in cases of gastrointestinal dysfunction or when EN is insufficient. Effective nutritional treatment requires a multidisciplinary approach, early intervention, and individualised therapy. Proper assessment of nutritional status using GLIM criteria and selecting the appropriate nutritional approach tailored to the stage of oncological treatment and the patient’s clinical condition are crucial.